Description of Time and Volume of Hydroxyethyl Starch 130/0.4 (6%) Fluid Administration to Restore Hemodynamics to Normal after Spinal Anesthesia in Cesarean Section - Juniansyah, Deby; Firdaus, Eza Kemal; Novitasari, Dwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hemodynamic variables such as blood pressure, mean arterial pressure (MAP), and pulse can change during cesarean section surgery performed under regional anesthesia. To stabilize the patient's hemodynamic status, colloid fluid treatment is administered because it has a longer half-life in the intravascular fluid. The research aims to understand the timing and volume of administering hydroxyethyl starch/HES 130/0.4 (6%) to restore hemodynamics to normal after spinal anesthesia in cesarean section surgery. The research method employs a quantitative study with an analytical observational design (cross-sectional). Data collection instruments include a hemodynamic observation sheet and a bedside monitor data measurement tool. This research was conducted over two months, from May to June. The sample for this research consists of 40 respondents using total sampling. The research location was conducted at Pusri Hospital in Palembang Indonesia. The study collected data by directly observing the respondents and recording the time and volume of hydroxyethyl starch 130/0.4 (6%) required for the hemodynamic status to return to normal. Data analysis was conducted using univariate analysis techniques. The results of the research analysis indicate that the time required for hemodynamic changes after spinal anesthesia has a standard deviation of 3.363, a mean value of 12.15, a maximum value of 20, and a minimum value of 5. HES 130/0.4 (6%), the amount of fluid given, and changes in blood flow after spinal anesthesia have a standard deviation of 30.783, a mean value of 99.65, a maximum value of 167, and a minimum value of 22.